Health for all a policy simulation for the financial sustainability of the Universal Health Care Act in the Philippines - Dy, Sheena Mae V. (School of Economics, University of the Philippines Diliman, 2018)
Reality shows us that many families still suffer from severe health expenditures that pushes them towards poverty. Thus, the World Health Organization and the United Nations have been encouraging countries to adopt a Universal Health Care (UHC) system, in which quality health becomes accessible without creating financial risk and harm for the person. Many countries have been transitioning to the said health policy that provides health services to all citizens of a country. Finally, last February 20, 2019, after years of evolving health policies, President Rodrigo Duterte signed the Republic Act 11223 or the Universal Health Care Act into law. However, the UHC is a huge undertaking for developing countries such as the Philippines. With the expansion of the population coverage of the Philippine health care system and the shift to a more preventive approach, several changes have to be made. This means incurring more costs and changing priorities, as most policies imply. The question of whether UHC in the Philippines, at its current state, is financially sustainable begs to be answered. Thus, this paper aims to use the Philippine National Health Accounts (PNHA) framework as the constraint to ensure financial sustainability while projecting the funds sourced and used to transition to a UHC system. In addition, this paper also provides policy recommendations to guide the implementing rules and regulation (IRR) of the law.